A anatomia e o ensino de anatomia no Brasil: a escola boveriana - Talamoni, Ana Carolina Biscalquini [UNESP]; Bertolli Filho, Claudio [UNESP] (Casa de Oswaldo Cruz, Fundação Oswaldo Cruz, 2019)
There is little scholarly research on the history, teaching and research of human anatomy in Brazil. A broader vision of the progress of anatomy under different circumstances in the country is virtually non-existent, leaving researchers keen to study the subject insecure. This is compounded by the fact that the data available are not always reliable. This text retraces the development of the discipline of anatomy and its research and education in Brazil in general and São Paulo state in particular, which can largely be reduced to the action of the self-proclaimed Boverian school of anatomy, founded by Italian physician Alfonso Bovero at the same time as the Medical Faculty of the University of São Paulo.

A história da anatomia humana, de sua pesquisa e seu ensino no Brasil é tema pouco explorado academicamente. Observa-se a quase inexistência de uma visão mais abrangente do percurso da anatomia contextualizada pelas contingências nacionais, o que gera insegurança entre os pesquisadores que buscam aprofundar-se nessa temática, majorada pelo fato de que muitos dos dados disponíveis nem sempre se apresentam suficientemente apurados. Este texto visa retraçar o desenvolvimento da disciplina anatômica – de sua pesquisa e seu ensino no contexto paulista e nacional –, em muito sintetizada pela ação da autoproclamada escola boveriana de anatomia, fundada pelo médico italiano Alfonso Bovero, por ocasião da criação da Faculdade de Medicina da Universidade de São Paulo.
Anatomy and the teaching of anatomy in Brazil: the Boverian school
Keywords: History of anatomy in Brazil; Teaching of anatomy; Boverian school of anatomy; escola boveriana de anatomia; ensino de anatomia; história da anatomia no Brasil